Can small-scale farming systems serve as an economic engine in the former homelands of South Africa? - Mathinya, V. N.; Franke, A. C.; van de Ven, G. W. J.; Giller, K. E. (Frontiers in Sustainable Food Systems, 2023)
Small-scale farming plays a critical role in the food security of Africa. An analysis of households in two former homelands provided critical insights into the future of small-scale farming in South Africa. From a survey of 132 households, 57 from Emmaus in the uKhahlamba local municipality in KwaZulu Natal Province and 75 from Thaba Nchu in the Mangaung Metropolitan municipality of the Free State province, indicators of food and nutrition security, income, and the relative contributions of on-farm versus off-farm sources to household welfare were calculated to determine if small-scale farming could drive the economy of these areas. Results revealed stark differences at household and regional levels and were attributed to the importance of crops versus livestock towards household welfare and the proximity of the regions to urban centres. This was demonstrated by more reliance on arable farming in Emmaus, unlike Thaba Nchu, where a nearby city allowed diversification of income portfolios. In both regions, labour constraints outweighed land limitations. It is, therefore, unlikely that increasing arable land of small-scale farmers alone will stimulate arable farming. On-farm production and consumption did not guarantee nutrition and food security. Currently, small-scale farming did not serve as an engine for economic growth in the communities and formed a small part of the income of most households. However, sustainable intensification of farm production is a plausible pathway for the small number of households for whom farming forms an important part of their income. These households have the potential to engage in more commercial activities if farming and policies can be aligned. A critical knowledge gap is how, under what context, and which forms of agricultural interventions may complement rural development efforts and contribute to the rural economy.